Interplay of fatty acids, insulin and exercise in vascular health - Kara C. Anderson; Jia Liu; Zhenqi Liu (Lipids in Health and Disease)
Abstract Fatty acid metabolism, exercise, and insulin action play critical roles in maintaining vascular health, especially relevant in metabolic disorders such as obesity, type 2 diabetes, and cardiovascular disease. Insulin, a vasoactive hormone, induces arterial vasodilation throughout the arterial tree, increasing arterial compliance and enhancing tissue perfusion. These effects, however, are impaired in individuals with obesity and type 2 diabetes, and evidence suggests that vascular insulin resistance contributes to the pathogenesis of type 2 diabetes and its cardiovascular complications. Elevated plasma levels of free fatty acids in people with insulin resistance engender vascular inflammation, endothelial dysfunction, and vascular insulin resistance. Importantly, these effects are both functionally and structurally dependent, with saturated fatty acids as the primary culprits, while polyunsaturated fatty acids may support insulin sensitivity and endothelial function. Exercise enhances fatty acid oxidation, reduces circulating free fatty acids, and improves insulin sensitivity, thereby mitigating lipotoxicity and promoting endothelial function. Additionally, exercise induces beneficial vascular adaptations. This review examines the complex interplay among fatty acid metabolism, exercise training-induced vascular adaptations, and insulin-mediated vascular changes, highlighting their collective impact on vascular health and underlying mechanisms in both healthy and insulin-resistant states. It also explores the therapeutic potential of targeted exercise prescriptions and fatty acid-focused dietary strategies for enhancing vascular health, emphasizing tailored interventions to maximize metabolic benefits. Future research should investigate the pathways linking fatty acid metabolism to vascular insulin resistance, with a focus on how exercise and dietary modifications can be personalized to enhance vascular insulin sensitivity, optimize vascular health, and reduce the risks of type 2 diabetes and associated cardiovascular complications.